Recapitulating porcine cardiac development in vitro: from expanded potential stem cell to embryo culture models - Rawat, Hilansi; Kornherr, Jessica; Zawada, Dorota; Bakhshiyeva, Sara; Kupatt, Christian; Laugwitz, Karl-Ludwig; Bähr, Andrea; Dorn, Tatjana; Moretti, Alessandra; Nowak-Imialek, Monika (Frontiers in Cell and Developmental Biology, 2023)
Domestic pigs (Sus scrofa) share many genetic, anatomical, and physiological traits with humans and therefore constitute an excellent preclinical animal model. Fundamental understanding of the cellular and molecular processes governing early porcine cardiogenesis is critical for developing advanced porcine models used for the study of heart diseases and new regenerative therapies. Here, we provide a detailed characterization of porcine cardiogenesis based on fetal porcine hearts at various developmental stages and cardiac cells derived from porcine expanded pluripotent stem cells (pEPSCs), i.e., stem cells having the potential to give rise to both embryonic and extraembryonic tissue. We notably demonstrate for the first time that pEPSCs can differentiate into cardiovascular progenitor cells (CPCs), functional cardiomyocytes (CMs), epicardial cells and epicardial-derived cells (EPDCs) in vitro. Furthermore, we present an enhanced system for whole-embryo culture which allows continuous ex utero development of porcine post-implantation embryos from the cardiac crescent stage (ED14) up to the cardiac looping (ED17) stage. These new techniques provide a versatile platform for studying porcine cardiac development and disease modeling.